(untitled) ("Journal "U". Economy. Management. Finance.", 2021)
The article presents the results of a study of investment activity in comparison of the Volga Federal District and the Russian Federation. The dynamics of the investment attractiveness of the regions that are part of the Volga Federal District is considered. Conclusions are drawn about the factors influencing the increase in investment activity of investors in the economy of the regions.